Transmission Kinetics and histopathology induced by European Turkey Coronavirus during experimental infection of specific pathogen free turkeys. Issue 1 (10th September 2018) - Brown, Paul A.; Courtillon, Céline; Weerts, Erik A. W. S.; Andraud, Mathieu; Allée, Chantal; Vendembeuche, Anthony; Amelot, Michel; Rose, Nicolas; Verheije, Monique H.; Eterradossi, Nicolas
Abstract: Numerous viruses, mostly in mixed infections, have been associated worldwide with poult enteritis complex (PEC). In 2008 a coronavirus (Fr‐TCoV 080385d) was isolated in France from turkey poults exhibiting clinical signs compatible with this syndrome. In the present study, the median infectious dose (ID50 ), transmission kinetics and pathogenicity of Fr‐TCoV were investigated in 10‐day‐old SPF turkeys. Results revealed a titre of 10 4.88 ID50 /ml with 1 ID50 /ml being beyond the limit of genome detection using a well‐characterized qRT‐PCR for avian coronaviruses. Horizontal transmission of the virus via the airborne route was not observed however, via the oro‐faecal route this proved to be extremely rapid (one infectious individual infecting another every 2.5 hr) and infectious virus was excreted for at least 6 weeks in several birds. Histological examination of different zones of the intestinal tract of the Fr‐TCoV‐infected turkeys showed that the virus had a preference for the lower part of the intestinal tract with an abundance of viral antigen being present in epithelial cells of the ileum, caecum and bursa of Fabricius. Viral antigen was also detected in dendritic cells, monocytes and macrophages in these areas, which may indicate a potential for Fr‐TCoV to replicate in antigen‐presenting cells. Together these results highlight the importance of good sanitary practices in turkey farms to avoid introducing minute amounts of virus that could suffice to initiate an outbreak, and the need to consider that infected individuals may still be infectious long after a clinical episode, to avoid virus dissemination through the movements of apparently recovered birds.